2013
DOI: 10.1007/s12663-013-0592-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Awareness of Speciality of Oral and Maxillofacial Surgery Amongst Medical Consultants of Vadodara District in Gujarat State

Abstract: Background and Aim Aim of this study was to survey the knowledge, attitude and awareness of the subject of oral and maxillofacial surgery speciality amongst the consultants and practitioners of medicine in district of Vadodara. Materials and Methods List of members of various specialities in medical faculty were obtained from Indian Medical Association, Baroda branch and staff members of medical colleges of Vadodara district. A questionnaire survey was made which was distributed and their options were noted. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Shah N et al studied the knowledge, attitude and awareness of speciality of oral and maxillofacial surgery amongst medical consultants. (Shah et al, 2015) In the present study, eventhough 86% and 82% of them were aware of the types of maxillofacial fractures, and LeFort I fracture is a maxillary fracture, respectively, only 40% were aware intermaxillary ixation as its management. Surprisingly, 44% and 35% of them reported that Le Fort I fracture causes disruption of the cribriform plate of the ethmoid bone and may be associated with cerebrospinal luid leak respectively, both are classic features of LeFort III fracture.…”
Section: Discussionmentioning
confidence: 49%
“…Shah N et al studied the knowledge, attitude and awareness of speciality of oral and maxillofacial surgery amongst medical consultants. (Shah et al, 2015) In the present study, eventhough 86% and 82% of them were aware of the types of maxillofacial fractures, and LeFort I fracture is a maxillary fracture, respectively, only 40% were aware intermaxillary ixation as its management. Surprisingly, 44% and 35% of them reported that Le Fort I fracture causes disruption of the cribriform plate of the ethmoid bone and may be associated with cerebrospinal luid leak respectively, both are classic features of LeFort III fracture.…”
Section: Discussionmentioning
confidence: 49%
“…OMFS is an internationally accepted surgical speciality. In some countries, like in the United States, it is an accepted speciality of dentistry; while in others, such as in the UK, it is a speciality that requires a degree in medicine [ 1 ]. In Saudi Arabia, the OMFS is recognised as a speciality branch of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of the OMFS improved from simple surgical procedures such as dentoalveolar surgeries and basic maxillofacial trauma to more advanced procedures like management of pathologies of head and neck (both benign and malignant), bone grafting, craniofacial surgery, TMJ surgery, cleft lip and palate, facial deformities correction, aesthetic facial surgery, implant surgery, etc [ 1 ] [ 5 ]. Also, OMFS deals with non - surgical difficulties affecting the orofacial area like the treatment of facial pain or oral mucosal disease [ 1 ] [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It includes facial cosmetic surgery, orthognathic surgery, cleft lip and palate surgery, head and neck cancer surgery, and facial trauma and reconstructive surgery. 2 OMFS is an internationally recognized surgical specialty. It is considered a branch of dentistry in countries such as the United States; because in the United Kingdom, it is considered a medical specialty.…”
Section: Introductionmentioning
confidence: 99%